Girls Education in Nepal: History, Challenging factors and Promoting Factors - Khatri, Hikamat Bahadur (HISAN: Journal of History Association of Nepal, 2022)
This study attempts to explore girls’ education history, challenging factors and promoting factors in. Similarly, it has raised the questions in girls’ education like how they are getting education .in different type d socio-cultural values and norms. Therefore, government made many efforts to create girls friendly environment in schools but it has not been achieved as we have targeted. So, how the parents’ biased mentality and socio-cultural mind hampers the girls’ education is the major concerning part of this study. It is found that some school and household related factors promote girls’ education. It is based on field data generated through interaction with participants.